The Bible and the university - Jeffrey, David Lyle, 1941-; Evans, C. Stephen (Grand Rapids, Mich. : Zondervan, 2007)
This book is the eighth in a series of books that result from annual conferences of the top evangelical hermeneutical scholars in the world. It is well known that the Western university gradually evolved from the monastic stadium via the cathedral schools of the twelfth century to become the remarkably vigorous and interdisciplinary European institutions of higher learning that transformed Christian intellectual culture in the thirteenth and fourteenth centuries. It is equally well known that subsequent disciplinary developments in higher education, including the founding and flourishing of many of the most prestigious of North American universities, owe equally to the Protestant and perhaps particularly Calvinist influence. But that the secularized modern university that descended from these developments is now in something of an identity crisis is becoming widely -- and often awkwardly -- apparent. The reason most often given for the crisis is our general failure to produce a morally or spiritually persuasive substitute for the authority that undergirded the intellectual culture of our predecessors. This is frequently also a reason for the discomfort many experience in trying to address the problem, for it requires an acknowledgement, at least, that the secularization hypothesis has proven inadequate as a basis for the sustaining of coherence and general intelligibility in the university curriculum. Nowhere is this more apparent than in the disciplines of biblical studies and theology, which once were the anchor or common point of reference for theological thought, but which are now both marginalized in the curriculum and internally divided as to meaning and purpose, even where the Church itself is concerned. In this final volume of the Scripture and Hermeneutic Series, a group of distinguished scholars have sought to understand the role of the Bible in relation to the disciplines in a fresh way. Offered in a spirit of humility and experimentally, the essays here consider the historic role of the Bible in the university, the status of theological reflection regarding Scripture among the disciplines today, the special role of Scripture in the development of law, the humanities and social sciences, and finally, the way the Bible speaks to issues of academic freedom, intellectual tolerance, and religious liberty. Contributors Include: Dallas Willard, William Abraham, Al Wolters, Scott Hahn, Glenn Olsen, Robert C. Roberts, Byron Johnson, Robert Cochran, Jr., David I. Smith, John Sullivan, Robert Lundin, C. Stephen Evans, David Lyle Jeffrey. - Publisher.
In this final volume of the Scripture and Hermeneutic Series, a group of distinguished scholars have sought to understand the role of the Bible in relation to the disciplines in a fresh way. Offered in a spirit of humility and experimentally, the essays here consider the historic role of the Bible in the university, the status of theological reflection regarding Scripture among the disciplines today, the special role of Scripture in the development of law, the humanities and social sciences, and finally, the way the Bible speaks to issues of academic freedom, intellectual tolerance, and religious liberty.
Introduction / David Lyle Jeffrey -- The Bible, the university, and the God who hides / Dallas Willard -- The place of Scripture in Christian theology / William J. Abraham -- No longer queen : the theological disciplines and their sisters / Al Wolters -- At the school of truth : the ecclesial character of theology and exegesis in the thought of Benedict XVI / Scott Hahn -- The spiritual sense(s) today / Glenn Olsen -- Situationism and the New Testament psychology of the heart / Robert C. Roberts -- The Bible, positive law, and the legal academy / Robert F. Cochran, Jr. -- Biblical imagery and educational imagination : Comenius and the garden of delight / David I. Smith -- Reading habits, Scripture and the university / John Sullivan -- The case for empirical assessment of biblical literacy in America / Byron Johnson -- 'As if God were dead': American literature and the question of Scripture / Roger Lundin -- Biblical literacy, academic freedom, and Christian liberty / David Lyle Jeffrey -- The Bible and the academy : some concluding thoughts and possible future directions / C. Stephen Evans.
Includes bibliographical references and indexes.
Keywords: Bible -- Influence; Education, Higher; Church and college; Universities and colleges -- Religion